ACTANTIAL SCHEMA AND FUNCTIONAL STRUCTURE OF THE FAIRY TALE "DIE GÄNSEMAGD" (THE GOOSE GIRL) OF THE BROTHERS GRIMM FAIRY TALE COLLECTION (ANALYSIS OF A. J. GREIMAS THEORY) - Eldaa Crystle Wenno; Henderika Serpara; Samuel Jusuf Litualy (JURNAL TAHURI, 2021)
This study aims to describe the actantial schema and functional structure of the German fairy tale "Die Gänsemagd". The method used in this research is a qualitative descriptive method. This method is used to determine the structure of actantial and functional models in the German fairy tale "Die Gänsemagd (The Goose Girl)" based on A. J. Greimas's theory. The data source in this study is a collection of German fairy tales by Brother Grimm (Deutsche Märchen von den Brüdern Grimm, Hauff, Beschstein und anderen) published by Artia Verlag, Prague in 1986. This study's data covered the unit of fairy tales that materialize in paragraphs, dialogues, and narratives of characters that show various conflicts following the research's objectives. The data were collected using documentation study techniques. Data analysis started by identifying the story's actantial and functional structure by reading the entire story content. After that, the actantial structure is determined by analyzing the characters' actions in the story to find their roles. The actantial structures that are determined are subject, object, opponent, assistant, and receiver. The analysis is continued by compiling a functional model by analyzing the story movement, which is divided into three parts; initial situation, transformation, and final situation. Based on the results of Greimas' narrative analysis of the German fairy tale "Die Gänsemagd," it can be concluded that there are two actantial schemas whose characters have several functions and roles in each schema. The first actantial schema consists of a subject, object, sender, receiver, assistant, with no opponent. Meanwhile, the second actantial schema consists of all the actants, namely, subject, object, sender, receiver, assistant, and opponent. The functional structure found in the story is the initial situation, the transformation (proficiency test stage, the main stage, and the glorious stage), and the final situation.